Perbedaan Konsumsi Cairan, Besaran Energi Minuman, dan Berat Jenis Urine pada Murid Kelas 4-5 Sekolah Dasar Negeri Sudimara 8 dan Sekolah Dasar Swasta Yadika 3 Ciledug - Aryani, Dian; Rahmawati, Siti Mutia; Ronitawati, Putri (Jurnal Nutrire Diaita (Ilmu Gizi), 2010)
AbstractWater is a major component of the body’s thermoregulatory system, substition of the body’s metabolism, for digestion, foodprocessing, muscle contractions, etc. The purpose of this study was to determine the differences between water consumption, total of energy drinks, and urine specific gravity in 4-5 grade student public primary school. The method used simple random sampling and the total of subject is 62 students. The data were collected such as; 1). Characteristics of sample: gender, age, Weight, Height, the amount of pocket money, knowledge about drinking water, and physical activity; 2). Consumption of water and energy drinks,taken from 3x24 hours food recall; 3). The density of urine, taken from the examination in the laboratory. The results shows the average consumption of water is 2097.9 ml (±152.241) for public primary school, whereas the private primary school is 2657.2 ml (±327.6); the total of energy drinks is 173.4 kcal (±82.8), it is from powder and tea drinks without packing, whereas the private primary school 434.7 kcal (±179.5), it is from milk without packaging, juice without bottled, and tea packaging; urine specific gravity in public primary school is 1022 (±7.7) 1whereas in private primary school is 1015 (±6.6). There are significant differences between water consumption (p<0.05), total of energy drinks (p<0.05), and urine specific urine specific gravity in 4-5 grade student public primary school (p<0.05). In public primary schools are still below the recomended intake of water requirement, therefore we should encourage student to increase their water consumption.Keywords: water consumption, total energy drinks, urine specific gravity AbstrakAir merupakan suatu komponen utama thermoregulatory system tubuh, pengganti metabolisme tubuh, untuk pencernaan, pengolahan bahan makanan, kontraksi otot, pengatur suhu tubuh, dll. Kebutuhan cairan anak usia 1-18 tahun relatif lebih besar. Tujuan penelitian ini adalah mempelajari perbedaan konsumsi cairan, besaran energi minuman, dan berat jenis urine murid kelas 4-5 sekolah dasar negeri dan sekolah dasar swasta. Pengambilan data dilakukan pada bulan Juni 2009. Cara pengambilan sampel dilakukan secara acak sederhana, sehingga total subjek di dapat 62 orang. Data yang dikumpulkan meliputi: 1)Karakteristik sampel: Jenis kelamin, umur, BB, TB, besaran uang saku, pengetahuan tentang air minum, dan aktivitas fisik; 2)Konsumsi cairan dan besaran energi dari minuman, diambil melalui food recall 3x24 jam; 3)Berat jenis urine,diambil melalui pemeriksaan di laboratorium. Hasil penelitian menunjukkan rata-rata konsumsi cairan sekolah dasar negeri 2097,9 ml (±152,241),sedangkan sekolah dasar swasta 2657,2 ml (±327,6); besaran energi minuman sekolah dasar negeri 173,4kkal (±82,8) berasal dari minuman serbuk dan teh tanpa kemasan, sedangkan sekolah dasar swasta 434,7kkal (±179,5) berasal dari susu tanpa kemasan, jus tanpa kemasan, dan teh kemasan; berat jenis urine sekolah dasar negeri 1022 (±7,7) sedangkan sekolah dasar swasta 1015 (±6,6). Ada perbedaan yang signifikan antara konsumsi cairan (t=8,622);(p<0,05), besaran energi minuman (t=7,362);(p<0,05), dan berat jenis urine pada murid kelas 4-5 sekolah dasar negeri dan sekolah dasar swasta (t=3,903);(p<0,05). Pada sekolah dasar negeri konsumsi cairan masih dibawah anjuran perlu di dorong untuk meningkatkan konsumsi cairan yang relatif tinggi.Kata kunci: konsumsi air, energi minuman, berat jenis urine